A Review on Charging Behavior of Electric Vehicles: Data, Model, and Control⁎***. Issue 5 (2020) - Jia, Qing-Shan; Long, Teng
Abstract: The adoption and usage of electric vehicles (EVs) have emerged recently due to the increasing concerns on the greenhouse gas issues and energy revolution. Relationship and interaction among EVs, charging stations, and micro grid have to be considered in the next generation of smart grid. Therefore, the topic of smart charging has been the focus of many works where a wide range of control methods have been developed. As one of the bases of simulation, the EV charging behavior and characteristics have also become the focus of many studies. In this extended abstract, we briefly review the charging behavior of EVs from the aspects of data, model, and control. For more detail, please refer to the published review paper with the same name. We provide the links for most of the data sets reviewed in this work, based on which interested researchers can easily access these data for further investigation.